2022
DOI: 10.3390/dairy3010014
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Dairy Milk: A Case Study Comparing Once- and Twice-a-Day Milking of Pasture-Fed Cows at Different Stages of Lactation

Abstract: In this case study, we compared the gross composition and fatty acid (FA) composition of milk from cows milked once a day (OAD) and twice a day (TAD) at different stages of lactation in real farm conditions with no control on feed. Seventy-two cows from a OAD milking herd and 181 cows from a TAD milking herd were sampled in early, mid and late lactation. Calibration equations were developed to enable the prediction of proportions of individual FAs using mid-infrared (MIR) spectroscopy. Cows milked OAD produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 42 publications
1
0
0
Order By: Relevance
“…Similarly, the proportions of de novo synthesis fatty acids, mainly C6:0–C14:0, were higher, and proportions of long-chain fatty acids were lower in cows milked OAD for all three genotypes compared to cows milked TAD. Similar results were reported by Sanjayaranj et al [ 39 ] in the previous work comparing fatty acid composition between cows milked OAD and TAD.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the proportions of de novo synthesis fatty acids, mainly C6:0–C14:0, were higher, and proportions of long-chain fatty acids were lower in cows milked OAD for all three genotypes compared to cows milked TAD. Similar results were reported by Sanjayaranj et al [ 39 ] in the previous work comparing fatty acid composition between cows milked OAD and TAD.…”
Section: Discussionsupporting
confidence: 91%
“…No significant differences in free fatty acid (FFA) profile were observed between OAD and TAD cheese at 180 days of maturation (Table 5). This result provides an interesting comparison with work already completed on FFAs and milking frequency, (Sanjayaranj et al 2022).…”
Section: Free Fatty Acid Profilesupporting
confidence: 52%
“…Most notably, Sanjayaranj et al (2022) observed differences in saturated fatty acid and de novo synthesised fatty acids between OAD and TAD, but it is essential to recognise that animal diet was not controlled within that work; indeed animal diet has already been shown to impact FFA profile in dairy products (O'Callaghan et al 2017). Within the experimental design for this research OAD and TAD, animals were all grazed on perennial ryegrass pastures and offered diets of similar quality to control this potentially confounding variable (Murphy et al 2023).…”
Section: Free Fatty Acid Profilementioning
confidence: 99%
See 2 more Smart Citations